2011
DOI: 10.1007/s00216-011-4920-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasmas produced by laser ablation using single and double pulses for food analysis demonstrated by probing potato skins

Abstract: We report on investigations of plasmas produced by laser ablation of fresh potatoes using infrared nanosecond laser radiation. A twin laser system consisting of two Nd:YAG oscillators was used to generate single or double pulses of adjustable interpulse delay. The potatoes were irradiated under ambient air with moderate pulse energies of about 10 mJ. The expansion dynamics of the ablation plume was characterized using fast imaging with a gated camera. In addition, time-resolved optical emission spectroscopy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…It requires little or no sample preparation and LIBS has the capability of measuring most of chemical elements [1,[5][6][7]. In regards to these advantages, LIBS is widely applied across many fields, such as analysis of art works and cultural heritage conservation [8,9], industrial applications for material processing control [10][11][12][13], quality insurance environmental protection [14,15]; and in medical field such as analyzing toxic substances [16,17]. A LIBS module has been integrated by NASA and ESA for their planetary exploration rovers to analyze soil on the Mars [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It requires little or no sample preparation and LIBS has the capability of measuring most of chemical elements [1,[5][6][7]. In regards to these advantages, LIBS is widely applied across many fields, such as analysis of art works and cultural heritage conservation [8,9], industrial applications for material processing control [10][11][12][13], quality insurance environmental protection [14,15]; and in medical field such as analyzing toxic substances [16,17]. A LIBS module has been integrated by NASA and ESA for their planetary exploration rovers to analyze soil on the Mars [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy (LIBS) stimulated strongly growing interest in the past years due to the capability of performing rapid multielemental analyses without or with minimized sample preparation [4,5]. Thus, the analytical capabilities of LIBS were investigated for various types of food such as wheat [6,7], cereals [8,9], vegetables [10,11], milk powder [12,13], and oil [14]. The presented approaches * Corresponding author: hermann@lp3.univ-mrs.fr that aim to quantify the elemental composition can be divided into three categories: (i) measurements based on calibration with standard samples; (ii) chemometric methods; (iii) calibration-free measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the application of CF-LIBS to organic materials encounters a supplementary difficulty that arises from matrix elements C, H, O and N. According to the atomic structures including large energy gaps between the electronic excitation levels, equilibrium Boltzmann distributions are hardly achieved for these elements [25,26]. The matrix elements are therefore generally ignored and CF-LIBS measurements are limited to a partial analysis of the elemental composition of food [17,12,18,11,19]. In the present paper, we present a method that improves the sensitivity of CF-LIBS, enabling thus the quantification of the full elemental composition.…”
Section: Introductionmentioning
confidence: 99%
“…However, some strategies have been developed [6][7][8][9] to improve the detectability of LIBS, which include the use of a spark for sample pre-ablation [10,11], spatial confinement of laser-induced plasma [12][13][14], use of a micro torch [15] and use of two (double-pulse) or more lasers pulses for plasma species excitation [16][17][18][19][20]. Some authors attribute the observed increase in sensitivity to the increment of temperature and electronic density of the plasma, an higher sample mass ablation and plasma reheating [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%